Why is Code Switching Still Used By Teachers in English Language Teaching? - Amanda, Finsya Rizky; Fediyanto, Niko; Ashurovna, Farmanova Dildora (Indonesian Journal of Education Methods Development, 2025)
This research involves issues of learning to use code switching in foreign language learning. In the context of Code switching, which focuses on the need for the use of code switching in teaching foreign languages in the classroom especially in vocational schools especially health majors. This report uses a descriptive qualitative method. Using interviews and transcripts. The report involved two different schools with each school having one teacher who participated with the study. The research revealed that teachers often use code-switching as a pedagogical strategy to facilitate communication with students. Given the students' limited English proficiency, code-switching emerged as an effective tool in the classroom. The analysis identified two main types of code-switching used: intra-sentential and inter-sentential. This practice not only aided better understanding and engagement, but also bridged the language gap, ensuring that students understood complex subject matter more effectively. The findings underscore the importance of code-switching in enhancing the learning experience in vocational health education environments. Highlighting : Code-switching supports comprehension in low English proficiency settings. Intra- and inter-sentential switching are the main types used. Enhances student engagement in vocational health classrooms. Keywords : Code switchings, Sociolinguistic, English foreign language, Vocational education, Classroom communication